Increasing Public Knowledge Through Leaflet Media to Prevent the Worsenal of Rheumatoid Arthritis in the Elderly - Norman Delvano Weky (International Journal Labs, 2025)
Rheumatoid Arthritis is one of the health problems experienced by the elderly. This disease is a chronic inflammation of the cell lining in the joints that causes pain, stiffness and swelling. This certainly interferes with the daily activities of the elderly, so educational efforts are needed for the elderly. The purpose of this study was to determine the increase in knowledge of the elderly after counseling about rheumatoid arthritis through leaflets in the Sikumana Community Health Center Working Area in 2025. This study used a one-group pretest-posttest design approach with a research sample of 50 research samples. The sampling technique used purposive sampling. Data analysis used the Wilcoxon Signed Rank Test to see the difference in pre-test and post-test levels of knowledge of the elderly after being given counseling. The results of this study showed an increase in the average knowledge of the elderly before and after being given counseling by 2.14 (pre=9.18; post=11.32). Statistical testing showed a difference in the level of knowledge of the elderly before and after (p value=0.000 <0.05) being given counseling through leaflets. Conclusion: Counseling for the elderly has been shown to have a positive impact, increasing knowledge about rheumatoid arthritis. Therefore, efforts are needed to continue educating the elderly and encouraging them to participate in all Prolanis activities.